Clinical Outcomes and PROMIS Scores with the Use of Synthetic Cartilage Implant (CARTIVA) in Hallux Rigidus at a Non-Industry Sponsored, Multi-Surgeon, Academic Institution. Issue 4 (16th October 2019) - Chapter, Megan C.; Garfinkel, Jonathan H.; Cabe, Taylor; Ellis, Scott; Roberts, Matthew; O'Malley, Martin; Elliot, Andrew; Levine, David S.; Deland, Jonathan; Demetracopoulos, Constantine; Drakos, Mark
Category: Midfoot/Forefoot Introduction/Purpose: Hallux rigidus is a common arthritic condition seen by foot and ankle specialists. Historically, surgical treatment options have varied from an isolated cheilectomy to first metatarsophalangeal joint fusion. More recently, first metatarsophalangeal (MTP) joint hemiarthroplasty with a polyvinyl alcohol (PVA) hydrogel implant (Cartiva) has become a popular surgical option. A randomized clinical trial sponsored by the manufacturers of the implant showed equivalent pain relief and functional outcome scores at 2 year follow-up when compared to patients undergoing first MTP fusion. In addition, the study reported no bone loss, implant wear or loosening. We retrospectively reviewed 1 year PROMIS score outcomes, clinical outcomes and implant survivorship of patients treated with first MTP hemiarthroplasty with the Cartiva implant at an academic, multi-surgeon center. Methods: We retrospectively reviewed 54 consecutive patients that underwent first MTP hemiarthroplasty with Cartiva for hallux rigidus between January 1, 2017 and December 1, 2017. Minimum follow-up criteria was 1 year, with the average being 1.37 years and maximum follow-up of 1.9 years. The Coughlin radiographic grading of disease severity averaged 2.18 at the time of implantation on a scale of 0 to 4. Surgery was performed by 8 fellowship-trained orthopedic foot and ankle surgeons at an academic institution. Baseline PROMIS scores (physical function, pain interference, global function, global mental, depression) and PROMIS scores acquired at 1 year postoperative were compared and evaluated using the Wilcoxon signed t-test. Clinical outcomes and postoperative complications/events were documented through review of electronic medical records. At the time of the study, 49 patients had reached 1 year follow-up with an average age of 56 (range, 33 - 74) years at the time of implantation. Results: Physical function, pain interference, global function and depression scores all demonstrated clinically and statistically significant improvement at 1 year postoperative. Global mental score did not show significant improvement at the one year follow-up. One patient underwent revision surgery to a 1st MTP fusion for persistent pain. Three patients had postoperative soft tissue swelling requiring prolonged retained sutures. Five patients underwent therapeutic injection with steroid between 2 - 11 months postoperative for persistent discomfort which improved. Five patients were prescribed orthotics between 3 - 6 months follow-up. One patient sustained a metatarsal fracture during the application of the implant requiring ORIF but retained the implant. Implant retention at 1 year was 98% (48/49). No correlation between preoperative radiographic grading and the incidence of poor clinical outcomes. Conclusion: To our knowledge, this is the first study that demonstrates the outcomes of synthetic cartilage implants using a large series of surgeons without affiliation or consultation for the implant company. One year following first MTP hemiarthroplasty with PVA hydrogel implant (Cartiva), functional and pain scores improved significantly, but did not show significant improvement with global mental scores. The implant displayed excellent survivorship at the 1 year time point, with only one patient undergoing surgical revision. Treatment of hallux rigidus with the PVA hydrogel implant - Cartiva, shows improved patient outcomes and has reassuring results at one year.